Dystrophic Cutaneous Calcification and Metaplastic Bone Formation due to Long Term Bisphosphonate Use in Breast Cancer - Ali Murat Tatlı; Seyda Gunduz; Sema Sezgin Göksu; Deniz Arslan; Mukremin Uysal; Cumhur İbrahim Başsorgun; Hasan Şenol Coşkun (Case Reports in Oncological Medicine)
Bisphosphonates are widely used in the treatment of breast cancer with bone metastases. We report a case of a female with breast cancer presented with a rash around a previous mastectomy site and a discharge lesion on her right chest wall in August 2010. Biopsy of the lesion showed dystrophic calcification and metaplastic bone formation. The patient’s history revealed a long term use of zoledronic acid for the treatment of breast cancer with bone metastasis. We stopped the treatment since we believed that the cutaneous dystrophic calcification could be associated with her long term bisphosphonate therapy. Adverse cutaneous events with bisphosphonates are very rare, and dystrophic calcification has not been reported previously. The dystrophic calcification and metaplastic bone formation in this patient are thought to be due to long term bisphosphonate usage.